AB0310 Predictive factors for the response to rituximab in rheumatoid arthritis: Results from a french university hospital. (23rd January 2014) - Couderc, M.; Mathieu, S.; Soubrier, M.
Abstract : Background: Positivity for rheumatoid factor (RF), anti–cyclic citrullinated peptide antibodies (anti-CCP) and high gamma globulin levels are predictive of better response to rituximab forrheumatoid arthritis (RA) [1]. Magnusson et al. showed a better response to RTX in patients with positive initial EBV load [2]. Objectives: To study the influence of several factors (FR, Anti-CCP, serum gamma globulin level, EBV load) on response to RTX. Methods: Patients treated by RTX for active RA in the rheumatology department of the university hospital of Clermont-Ferrand (France) between April 2006 and May 2011 were prospectively included. RF, anti-CCP, gamma globulin level and EBV load were measured before the first RTX cycle. Clinical response were analysed 6 months after RTX according to the criteria the European league against rheumatism (EULAR). Univariate and multivariate analyses were performed to identify factors associated with response to RTX at 6 months. Results: Sixty-four patients (51 women (79.7%), mean age =61.2 years) were included. Mean disease duration was 16.4 years and 46 patients (71.8%) had already received one or more anti-TNF treatments. At 6 months, 46 patients (71.8%) had moderate-to-good response to RTX. Thirty-seven patients, of whom 6 were positive, had EBV-load measure before RTX. After 6 months, all were negative. Positivity for RF (odds ratio 0, 53 [95% confidence interval O, 1-2, 8]), or positive initial EBV load (odds ratio 0, 2 [95% confidence interval 0, 03 – 1, 3])were not associated with good-to-moderate response. Positivity for anti-CCP was associated with good-to-moderate response (odds ration 4, 3 [95% confidence interval 1, 2 – 15, 7]). High level of gammaglobulin (>12g/L) was correlated with non-response to RTX (odds ratio 0, 05 [95% confidence interval 0, 03-0, 66]). Conclusions: In contrast with precedent studies, high level of gamma globulins was predictive of worth response to RTX and only anti-CCP antibodies were correlated to a better response. References: Sellam J, Hendel-Chavez H, Rouanet S, Abbed K, et al. B cell activation biomarkers as predictive factors for the response to rituximab in rheumatoid arthritis: a six-month, national, multicenter, open-label study. Arthritis Rheum. 2011;63:933-8. Magnusson M, Brisslert, Zendjanchi K, Lindh M, Bokarewa MI. Epstein-Barr virus in bone marrow of rheumatoid arthritis patients predicts response to rituximab treatment. Rheumatology (Oxford). 2010;49:1911-9. Disclosure of Interest: None Declared